THE SURVEY OF NUMERICAL METHODS APPLICATION IN ENGINEERING EDUCATION - Othman, Zuraini; Shibghatullah, Abdul Samad; Kasmin, Fauziah; Syed Ahmad, Sharifah Sakinah (2008)
Numerical methods are the study of algorithms for the problems of continuous mathematics in different field including engineering education. The objective of numerical methods is the design and analysis of techniques to give approximate but accurate solutions to hard problems. Ways of computation of numerical methods are either manual or using mathematical software. Manual way of calculation ts hard takes time, and prone to error. Currently, there are mathematical software available in market such as matlab and Maple that are being used in engineering education. However, the limitations with the existing software are that they are expensive, very general and not user-friendly. There are some commands that user needs to learn in order to generate the answer and different software had different command. It becomes difficult when the mathematical problem is complicated Therefore, this research aims to produce mathematical engineering education software that is customized to speciﬁc need of students, lecturers, and researchers and more user-friendly. This paper presents a survey of numerical method application in engineering education to ﬁnd out the most common calculation used by students, lecturers and researchers and to identity their requirements of good numerical methods software. The ﬁnding will be used as a basis to develop a numerical methods engineering education software that fulfills the requirement of users.